2023
DOI: 10.1007/s11356-023-26860-2
|View full text |Cite
|
Sign up to set email alerts
|

Citrus fruit residues as alternative precursors to developing H2O and CO2 activated carbons and its application for Cu(II) adsorption

Abstract: Due to its toxicity, the presence of Cu(II) ions released in aquatic environments presents a serious threat to the environment and human health. In search of sustainable and low-cost alternatives, there are citrus fruit residues, which are generated in large quantities by the juice industries and can be used to produce activated carbons. Therefore, the physical route was investigated for producing activated carbons to reuse citrus wastes. In this work, eight activated carbons were developed, varying the precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…The surface area values found in this work are lower than most of the activated carbons. However, these values are in the order of other carbon adsorbents obtained from different natural residues reported in the literature: da Silva et al [5] found surface area values in the range 166-400 m 2 /g for carbons obtained from citrus fruit residues, Verma et al [11] found values of 207 m 2 /g and 37 m 2 /g for carbon adsorbents derived from waste biomass of citrus limetta (peel and pulp), Kumar et al [6] found 67.5 m 2 /g for biochars obtained from orange peel residues, Ahmadian et al [2] found 195 m 2 /g for biochars obtained from lemon peel and Aboli et al [50] found 7.2 m 2 /g for carbons prepared from citrus limetta leaves. It should be remarked that the impregnation step, the mixture of the carbonaceous precursor with FeCl 3 , is usually performed by two different methods: in an aqueous solution or by physical mixing between the carbon precursor and the iron chloride activating agent.…”
Section: Adsorbents Characterizationmentioning
confidence: 66%
See 1 more Smart Citation
“…The surface area values found in this work are lower than most of the activated carbons. However, these values are in the order of other carbon adsorbents obtained from different natural residues reported in the literature: da Silva et al [5] found surface area values in the range 166-400 m 2 /g for carbons obtained from citrus fruit residues, Verma et al [11] found values of 207 m 2 /g and 37 m 2 /g for carbon adsorbents derived from waste biomass of citrus limetta (peel and pulp), Kumar et al [6] found 67.5 m 2 /g for biochars obtained from orange peel residues, Ahmadian et al [2] found 195 m 2 /g for biochars obtained from lemon peel and Aboli et al [50] found 7.2 m 2 /g for carbons prepared from citrus limetta leaves. It should be remarked that the impregnation step, the mixture of the carbonaceous precursor with FeCl 3 , is usually performed by two different methods: in an aqueous solution or by physical mixing between the carbon precursor and the iron chloride activating agent.…”
Section: Adsorbents Characterizationmentioning
confidence: 66%
“…Nowadays, agricultural and food processing activities generate huge amounts of solid wastes, which are commonly eliminated by burning, bringing on different ecological and environmental problems [1]. Agricultural waste is cheap, and it includes husks, peels, and shells of different crops such as rice, sunflower, palm, citric, or different kinds of nuts [2][3][4][5][6]. Most of this waste contains such compounds as starch and lignocellulosic biomass including cellulose, hemicellulose, and lignin [7,8], all of them with a high content of carbon, and were easily transformed into activated carbons or biochar under pyrolysis processes [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the asymmetrical stretching vibrations of C-O within polysaccharides correlate with the peaks at 1041 and 1038 cm −1 [18]. In comparison to untreated vermicompost, a discernible attenuation in the intensity of the absorption band corresponding to the aromatic C=C bond is observed in vermicompost post-Cu 2+ adsorption, imputed to the interaction between the delocalized π electrons inherent in aromatic structures and Cu 2+ [21]. The absorption bands associated with O-H and C-O bonds also exhibit a diminution in intensity post-Cu 2+ adsorption, with the primary impetus for this transformation potentially residing in the occurrence of chelation between Cu 2+ and oxygen-bearing functional groups [22].…”
Section: Resultsmentioning
confidence: 99%